Pengaruh Pengalaman Pelanggan dan Nilai yang Dirasakan terhadap Kepuasan Wisatawan Pengguna Bus City Tour Sidoarjo - Anisa Nur Fadilla; Meirinawati Meirinawati; Eva Hany Fanida; Fitrotun Niswah (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
This study aims to analyze the influence of customer experience and perceived value on tourist satisfaction among users of the Sidoarjo City Tour Bus as a form of public tourism transportation service. The Sidoarjo City Tour Bus represents a regional government service innovation intended to support tourism development while improving urban tourism accessibility. This study employs a quantitative approach using a survey method involving tourists who used the Sidoarjo City Tour Bus. Data were collected through questionnaires distributed to 99 respondents and analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that customer experience does not have a significant effect on tourist satisfaction, suggesting that the experiences perceived by users are still subjective and not consistently felt by all service users. In contrast, perceived value has a positive and significant effect on tourist satisfaction, making it the most dominant variable in influencing satisfaction among Sidoarjo City Tour Bus users. These findings indicate that tourist satisfaction is more strongly determined by perceptions of benefits, service quality, and the suitability between sacrifices made and benefits received rather than by emotional experience alone. Therefore, this study recommends that the management of the Sidoarjo City Tour Bus and the local government enhance service value through improvements in facilities, information systems and registration processes, as well as optimization of comfort and schedule certainty. These efforts are important to increase tourist satisfaction and to support sustainable tourism development in Sidoarjo Regency.